2019
DOI: 10.1016/j.ijggc.2019.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of H2O on the volatilization characteristics of arsenic during isothermal O2/CO2 combustion

Abstract: The effect of H 2 O on the volatilization behavior of arsenic in coal was studied under O 2 /CO 2 combustion conditions at 800-1300 ºC, which covers the effective range of coal combustion temperatures appropriate for conventional coal combustion technologies. By controlling the combustion time of coal, the volatilization percentage and rate of As versus time were obtained. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) analyses were used to study the evolution of minerals with and without H 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…The solid samples (raw coal and residue after sequential chemical extraction) must be digested before measurement to obtain the concentration of arsenic. More details on the digestion procedures can be found elsewhere [17,26].…”
Section: Sample Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The solid samples (raw coal and residue after sequential chemical extraction) must be digested before measurement to obtain the concentration of arsenic. More details on the digestion procedures can be found elsewhere [17,26].…”
Section: Sample Analysis Methodsmentioning
confidence: 99%
“…S1 in Supporting Information. The description of the combustion system and experimental procedure are described in our previous work [17].…”
Section: Combustion Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Each coal sample utilized weighed approximately 0.08 g with a precision of ±0.0001 g. The total gas flow rate was 2.67 L/min. Our prior research demonstrated that the gas flow rate of 2.67 L/min can mitigate the impact of external diffusion on experimental outcomes. At least three experiments per group were conducted to reduce experimental errors. Table shows the detailed experimental conditions.…”
Section: Methodsmentioning
confidence: 99%